Aqueous Aluminum‐Carbon Rechargeable Batteries. Issue 4 (31st December 2021) - Smajic, Jasmin; Hasanov, Bashir E.; Alazmi, Amira; Emwas, Abdul‐Hamid; Wehbe, Nimer; Genovese, Alessandro; El Labban, Abdulrahman; Costa, Pedro M. F. J.
Abstract: Carbon cathodes have shown excellent electrochemical behavior in aluminum batteries based on non‐aqueous electrolytes. By contrast, their use in Al systems operating in a salt‐water medium is plagued by poor and unstable performance. Herein, it is sustained that a successful C cathode for rechargeable aqueous Al batteries requires surface customization to enable hydrophilicity and grafting of charged Al molecules. Employing a freeze‐dried reduced graphene oxide (rGO) as the active electrode material, an aqueous Al‐C battery is assembled with a high energy density (136 Wh kg −1 per cathode mass) and one of the best capacity retentions reported (≈60% across a range of current densities and constant Coulombic efficiencies close to unit). Furthermore, the rGO cathode more than doubles the benchmark for life cycles (to ≈200 cycles) and can be charged rapidly (<5 min). To explain this response, a charge storage mechanism is proposed wherein the [Al(H2 O)6 ] 3+ ions do not get desolvated when inserted into the cathode. The guest Al ions (surface adsorbed or intercalated) act as proton donors and may get anchored on the oxygen moieties of the rGO, further promoting the formation of an electrochemical double layer. A mixed charge‐storage regime follows that stabilizes the carbon cathode and enables an unprecedented response. Abstract : Reduced graphene oxide is used as a cathode material for aqueous aluminum batteries. With high energy density, high Coulombic efficiency and fast‐charging capabilities, the cell exhibits a substantially improved electrochemical performance over other aluminum‐carbon cells. The hydrophilicity of the carbon is a critical parameter enabling these results, through a mixed charge‐storage mechanism.